Unsettled times: shaded polychrome paintings and hunter-gatherer history in the southeastern mountains of southern Africa - Mazel, A. D. (Southern African Humanities, 2021)
New information generated during the last two decades has allowed us to review previous conclusions that the shaded polychrome paintings of the southeastern mountains were done during the last few hundred years. This new data derives from the relative and absolute dating of rock art in KwaZulu-Natal and the excavation of rock shelters. It is supported by an assessment of the earlier rock art sequencing work done by Pager and Vinnicombe. Drawing together these different strands of evidence, it is proposed that shaded polychrome paintings emerged in the southeastern mountains around 2000 years ago and, with few exceptions, lasted until 1600 years ago in the northern KwaZulu-Natal Drakensberg. The terminal date for shaded polychromes elsewhere in the southeastern mountains is not known and requires additional research. It is submitted that these paintings relate to a phase of hunter-gatherer history which was characterised by increased stress and ritual activity associated with substantial social and cultural changes that resulted from the movement of agriculturist communities into southern Africa. To cite this article: Mazel, A.D. 2009. Unsettled times: shaded polychrome paintings and hunter-gatherer history in the southeastern mountains of southern Africa. Southern African Humanities 21: 85-115.